Abnormal Stress‐Related Measures of Arterial Stiffness in Middle‐Aged and Elderly Men and Women With Impaired Fasting Glucose at Risk for a First Episode of Symptomatic Heart Failure. Issue 1 (14th January 2015) - Vasu, Sujethra; Morgan, Timothy M.; Kitzman, Dalane W.; Bertoni, Alain; Stacey, Richard B.; Hamilton, Craig; Chiles, Caroline; Thohan, Vinay; Hundley, W. Gregory
Abstract : Background: Abnormal resting arterial stiffness is present in middle‐aged and elderly persons with abnormalities of fasting glucose (diabetes or impaired fasting glucose) and is associated with exercise intolerance. We sought to determine whether these same persons exhibited stress‐related abnormalities of arterial stiffness. Methods and Results: We analyzed dobutamine magnetic resonance stress imaging results from 373 consecutively recruited persons aged 55 to 85 years with normal fasting glucose, impaired fasting glucose, or diabetes who were at risk for but without symptomatic heart failure. Personnel blinded to participant identifiers measured arterial stiffness (brachial pulse pressure/left ventricular stroke volume indexed to body surface area, the aortic elastance index [brachial end‐systolic pressure/left ventricular stroke volume indexed to body surface area], and thoracic aortic distensibility) at 80% of the maximum predicted heart rate response for age. Participants averaged 69±8 years of age; 79% were white, 92% were hypertensive, and 66% were women. After accounting for hypertension, sex, coronary artery disease, smoking, medications, hypercholesterolemia, and visceral fat, we observed an effect of glycemic status for stress measures of arterial stiffness in those with diabetes and impaired fasting glucose relative to those with normal fasting glucose ( P =0.002, P =0.02, and P =0.003, respectively). Conclusion: Middle‐ and older‐aged individuals with diabetes or impaired fasting glucose have higher stress measures of arterial stiffness than those with normal fasting glucose. These data emphasize the need for future studies with larger sample sizes to determine whether stress‐related elevations in arterial stiffness are related to exercise intolerance and future episodes of heart failure experienced by those with abnormalities of fasting glucose. Clinical Trial Registration: URL:http://clinicaltrials.gov/ . Unique identifier: NCT00542503.